Embedding dementia research in clinical practice: Progress of the Oxford Brain Health Centre. (31st December 2021) - O'Donoghue, M Clare; Blane, Jasmine; Mitchell, Robert; Aikin, Nicola; Lindsay, Karen; Campbell, Jon; Semple, Juliet; Raymont, Vanessa; Martos, Lola; Mackay, Clare
Abstract: Background: Launched in August 2020, the Oxford Brain Health Centre (BHC) is the UK's first psychiatry‐led joint clinical‐research service providing high‐quality assessments and increasing research opportunities for patients with memory problems. By embedding research in the NHS service, the BHC aims to address gaps between clinical practice and research advances into dementia. This abstract describes the first 60 referrals from the BHC pilot. Methods: Patients from Oxford Health NHS Foundation Trust memory clinics were referred to the BHC for assessment prior to their diagnostic appointment. At the BHC, patients completed clinical assessments ‐ MRI scan, cognitive assessment and questionnaires – and could consent to use of clinical data for research, additional research assessments, and recontact about future research. Accompanying relatives completed a clinical informant interview and could consent to recontact about research. Patient/relative feedback was obtained via questionnaires. Results: Between August and December 2020, the BHC received 60 referrals. 38% were returned to the memory clinic for reasons relating to the patient (n=9, e.g. patient unable to travel to the centre), the referral (n=3, e.g. patient already seen in clinic), or the MRI scan (n=11, e.g. claustrophobia, MR contraindication). BHC appointments occurred on average 26 days (range: 5‐63) after referral from the memory clinic. Only 3% did not attend. Of the 33 attendees in 2020, 58% were female, average age was 77.5 years (66‐90), and average ACE‐III score was 66.8 (9– 98; max: 100). 97% of patients consented to use of clinical data for research, 88% to additional research assessments, and 69% to recontact about research. 81% of relatives consented to recontact about research. Service‐user feedback was consistently high; 100% of responding patients were satisfied with the BHC service, particularly highlighting positive interactions with staff. Conclusions: Since launching, we have demonstrated the feasibility of an integrated clinical‐research service for people with memory problems and demonstrated extremely high research uptake in this population. Evaluation of referrals, procedures, impact on diagnosis, and health economics at the end of the 6‐month pilot will inform sustainability and scalability of Oxford BHC to provide a model for a specialist service that can be adopted throughout the NHS.